1996
DOI: 10.3177/jnsv.42.567
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term 'Corn Pepffde' Ingestion on Alcohol Metabolism in Stroke-Prone Spontaneously Hypertensive Rats with Alcohol Loading.

Abstract: SummaryThe effect of long-term `corn peptide (CP)' ingestion on alcohol metabolism was investigated in stroke-prone spontaneously hyper tensive rats (SHR-SP) with alcohol loading. Long-term CP ingestion in the EtOH/CP group did not significantly increase plasma GOT and GPT activities but markedly increased hepatic ADH and ALDH activities. Intragastric CP administration prior to a dose of 1.0 g/kg ethanol signifi cantly lowered the blood ethanol concentration in SHR-SP which had been loaded with ethanol for a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Glutamic acid, leucine, alanine and proline are rich in both CPS and ZPS. These results agreed with previous reports (Yamaguchi et al. 1996b, 1997; Li et al.…”
Section: Resultssupporting
confidence: 94%
“…Glutamic acid, leucine, alanine and proline are rich in both CPS and ZPS. These results agreed with previous reports (Yamaguchi et al. 1996b, 1997; Li et al.…”
Section: Resultssupporting
confidence: 94%
“…Many studies have been devoted to the preparation of new corn‐derived bioactive peptides to facilitate alcohol metabolism (Ma et al., ; Wang et al., ; Yu et al., ). Yamaguchi, Nishikiori, Nozaki, Ito, and Furukawa () found that long‐term intake of CPs could markedly increase hepatic ADH and ALDH activities, contributing to the transitions from alcohol to acetaldehyde and from acetaldehyde to acetate, respectively. CPs can supply the NAD + content by consuming Ala, Leu, and Pro, and slow the absorption rate of alcohol via the gastrointestinal membrane (Yamaguchi, Nishikiori, Ito, & Furukawa, ).…”
Section: Biological Activities and Corresponding Mechanisms Of Bioactmentioning
confidence: 99%
“…As shown in Figure , CPs facilitate alcohol metabolism via several key mechanisms, including (1) the reduction of oxidative stress during ethanol oxidation via eliminating oxygen, superoxide anions, and hydroxyethyl radicals (Wang et al., ; Wu et al., ); (2) activating hepatic ADH and ALDH, which can reduce the serum alcohol concentration (Yamaguchi et al., ; Yu et al., ); and (3) modulating the NADH/NAD + ratio to change the redox system and slowing the absorption rate of alcohol to prevent a dramatic increase in serum alcohol level (Yamaguchi et al., ).…”
Section: Biological Activities and Corresponding Mechanisms Of Bioactmentioning
confidence: 99%
“…It is likely that the effect of CP ingestion on facilitating alcohol metabolism may be due not only to the potential supply ofNAD + by the metabolism of alanine, leucine, and proline from CP, but also to the delay of release of ethanol from the stomach or malabsorption of ethanol in the gastrointestinal tract. 2) Concerning alcohol metabolism in animals, the ability to metabolize alcohol is affected by nutritional conditions and the rats fed with a low protein diet had poorer ability for alcohol metabolism due to the deficiency of amino acids, especially essential amino acids. 3 .…”
mentioning
confidence: 99%
“…2 ) CP is an oligopeptide produced by proteolysis using alkaline protease from alkalophilic Bacillus A-7, which is the product of Nihon Shokuhin Kako Co., Ltd., Japan. It is likely that the effect of CP ingestion on facilitating alcohol metabolism may be due not only to the potential supply ofNAD + by the metabolism of alanine, leucine, and proline from CP, but also to the delay of release of ethanol from the stomach or malabsorption of ethanol in the gastrointestinal tract.…”
mentioning
confidence: 99%